Tahfidz Management Pesantren Darut Tilawah Ponorogo Jawa Timur Indonesia - Sanudin Sanudin; Katni Katni; Anip Dwi Saputro (Ruhama : Islamic Education Journal, 2021)
This research discusses the management of the Al-Qur'an tahfidz program at the Darut Tilawah Islamic Boarding School Muneng Balong Ponorogo, East Java, Indonesia. Includes planning, implementation and evaluation. The research method used in this research is a qualitative method by collecting data through interviews, documentation and observation. The findings of this study can be concluded 1). Planning for the Tahfidz Al-Qur'an program at the Darut Tilawah Muneng Balong Ponorogo Islamic Boarding School is divided into two, namely: Boadring School Management and Tahfidz Program Management specifically from the aspect of educators, infrastructure, and evaluation. 2). The process of implementing the Tahfidz Al-Qur'an program at the Darut Tilawah Muneng Balong Ponorogo Islamic Boarding School uses the repetition method, the guidance technique and the rest of the time in one room. After dhuhur one juz, before Asr prayer half juz after Ashr prayer read bi nadzor simultaneously per class muroja'ah for two hours totaling half juz, after isya' muroja'ah two hours amounting to half juz. 3). evaluation of recitation of the Qur'an is carried out twice. a. Every day after dawn. b. Once every semester and it is called the tahfidz quarantine program. The aspects that are assessed are: aspects of fluency memorization, recitation, fashahah and morals or attitudes.